THE POTENTIAL OF DIGITIZING THE ISTISHNA CONTRACT DURING A PANDEMIC COVID-19 IN INDONESIA - Salwa, Yassindya; Arifin, Muhammad Iqbal; Fageh, Achmad (The Pontianak State Institute of Islamic Studies, 2024)
The current istishna contract has experienced an event of digitization and adaptation to the buying and selling activities of the public, especially in Indonesia, namely by utilizing an online or network-based system. During the Covid-19 pandemic, it was not uncommon to find several businesses implementing the istishna contract as a manifestation of the digitization of buying and selling contracts. However, it is still not known for sure whether the istishna contract has the potential to be adequately implemented by the teachings of Islamic law or not, especially in the digitalization era, which adapts the istishna contract into an Islamic-based transaction activity that uses various information technology facilities. This research is qualitative research with the retrieval method of information utilizing a literature study. Thus, in finding conclusions on the problems discussed, the author uses a normative approach that examines the issue according to the views of norms, one of which is religious norms related to the permissibility and opportunities of digitizing the istishna contract in Indonesia. In addition, the author analyzes the impact of the pandemic on the economy, which is, of course, related to the potential for the istishna contract. This study aimed to determine the potential for digitizing the istishna contract, especially during the Covid-19 pandemic. From this research, the conclusion is that the istishna contract has the potential to be quite good in the community's economic activities during the Covid-19 pandemic, even though it is in the form of digitalization.